The role of growth and maturation during adolescence on team selection and long-term sports participation - Dale, D. R. (University of Saskatchewan, 2018)
Background: Increases in growth and maturation result in physiological improvements, which influence performance. Older, more mature athletes are often seen as more talented and selected onto teams. Those born early in the selection year (termed relative age (RA)) have an advantage over those born later. Little is known as to whether selection onto a team influences an individual`s long-term sports participation. The aims of this study were; (i) to investigate the relationship of RA, anthropometrics, and maturity to team selection and (ii) to investigate the long-term (3 years) consequence of selection on sports participation. Methods: 851 participants (580 male and 271 female) were recruited at bantam level sport tryouts in six team sports (soccer, hockey, football, basketball, volleyball, and baseball). Individuals` date of birth, date of test, height, sitting height and weight were measured. Parental height was acquired. Age at peak height velocity (APHV) and predicted final height were estimated. Current sports participation was acquired via questionnaire. For analysis, athletes were grouped by team-selection, sex, sport and birth month quartiles. Birth month quartile analysis was done via chi-square goodness of fit test. Growth and maturation differences between selected and not selected groups was done via one-way ANOVA. Results: In the whole sample, first and second birth month quartiles were overrepresented (p < 0.05). Apart from female soccer, male hockey and male basketball players (p < 0.05), no relationships were found between birth month and team selection (p > 0.05). Male selected soccer players were significantly shorter and male selected hockey players were significantly taller (p < 0.05) than their non-selected counterparts. In soccer, basketball, and volleyball, selected athletes are more likely to continue in the sport, and not selected athletes are more likely to change sports. Discussion: While some differences exist between the growth and maturation of selected and not selected athletes during bantam tryouts, most sports appear not to be influenced. However, it would appear that, as a whole, athletes attending these tryouts already showed some bias in their dates of birth and anthropometrics. Over a 3-year period, sports selection did not appear to have a relationship with sports participation.